e-Restoration of Faces Appearing In Cultural Heritage Artefacts - Stylianou, Georgios; Lanitis, Andreas (My University, 2009)
Virtual restoration of Cultural Heritage (CH) artefacts is an important task that aims to re-create the original appearance of damaged items. In this paper we describe a method that can be used for virtual restoration of faces appearing in cultural heritage artefacts. Given a damaged face appearing in a 2D image we estimate the complete 3D shape of a face using data from the non-damaged face and we predict the texture of the damaged regions. As a result it is possible to generate a restored 3D model of the face which can be mapped back on the 2D image in order to complete the restoration process. Both visual and quantitative results prove the potential of the proposed method.